Impact of IL-2 on Treatment Tolerance in Patients With High-Risk Neuroblastoma Treated With Dinutuximab Beta-Based Immunotherapy - Filiz Cicek (Frontiers in Pediatrics, 2020)
Patients with high-risk neuroblastoma treated with continuous long-term infusion of anti-GD2 antibody dinutuximab beta (DB) in combination with IL-2 show an acceptable safety profile. Here, we compared treatment tolerance with and without IL-2. Ninety-nine patients with high-risk neuroblastoma received up to five cycles of DB given as long-term infusion (10 mg/m2/d, 100 mg/m2; per cycle) with IL-2 (53 patients; regimen A; 6 × 106 IU/m2/d; 60 × 106 IU/m2/cycle) and without IL-2 (46 patients; regimen B) in a single-center compassionate use program. Clinical parameters (body temperature, vital signs, Lansky performance score), laboratory values [C-reactive protein, IFN-γ, IL-6, and IL-18 (cycle 1)], and requirement of i.v. co-medication (e.g., morphine, metamizole) were systematically assessed. Patients with stable clinical parameters and that did not require co-medication were defined as potential “outpatient candidates.” Patients showed higher levels of body temperature and CRP in regimen A compared to B. However, IL-6 serum concentrations were similar in pts of both cohorts in the first cycle. Patients receiving regimen B showed a shorter time to achieve normal vital parameters and required less co-medication compared to patients in regimen A that resulted in a shorter median time period to discharge and to achieve a potential outpatient status (6d regimen A and 3–5d regimen B after start of antibody infusion, respectively). This study shows that omitting IL-2 from immunotherapy with DB allows reduced co-medication and hospitalization time and therefore results in improved quality of life in patients with high-risk neuroblastoma.